“Análisis Jurídico y Doctrinario del Conflicto de Competencias Jurisdiccionales entre la Justicia Indígena y Justicia Ordinaria en el Juzgamiento de Delitos de Acción Penal Pública”. - Suing Ochoa, Guissell Stefany (2024)
The present Curricular Integration Work entitled: "Legal and Doctrinary Analysis of the Conflict of Jurisdictional Competences between the Indigenous Justice and Ordinary Justice in the Judgment of Crimes of Public Criminal Action". The interest that leads us to develop this research is due to the fact that at the moment of application of the indigenous justice in the trial of their internal behavior, it could be evidenced the arrogation of functions for sanctioning behavior that have a judicial protection of criminally protected legal goods and that in addition to this, the overreach of their sanctions led to a great direct fault to our Constitution of the Republic of Ecuador (CRE) and the Human Rights recognized by our country, In view of this fact, there is a need to establish clear delimitations and procedures with respect to the powers that the indigenous justice system has to sanction certain types of developments in terms of the matter and in relation to the people involved, with respect to the powers of the Ordinary Justice System. During the development of this work I have been able to verify that the existence of the problem lies in the conflict of coexistence of two legal systems in our country since at the time of applying justice in cases of crimes of public criminal action in which members of indigenous communities, peoples or nationalities have intervened or been affected, according to the law, they do not have full access to the legal apparatus because there is a legal vacuum in terms of procedural rules in case of intervention of indigenous justice in criminal matters, sometimes falling back on the breach of constitutional norms, This has generated a conflict of jurisdictional competencies at the moment of judging this type of crimes in which one of the procedural parties is part of these communities, thus causing an imbalance in our country at the moment of applying justice, although it is true that neither of the two systems have been able to effectively guarantee the exercise and enjoyment of the rights of Ecuadorian citizens belonging to indigenous communities, people and nationalities, since the overreach of power of the indigenous justice system infringes due process and full reparation to the victim, while the ordinary justice system acts belatedly due to the lack of procedural regulations and delimitation of jurisdiction and competence of the indigenous justice system in criminal matters, which has resulted in the effective defenselessness of the parties to the proceedings, thus affecting their constitutional rights. It should be emphasized that this research includes a broad analysis of legal information, from a descriptive, evaluative, explanatory and propositional perspective, under a legal guideline in constitutional, criminal and comparative law, also used materials and methods that allowed the development of the research, likewise interviews and surveys were conducted with legal professionals, whose results are aimed at awakening a critical view regarding the breach of the rights of the procedural parties in crimes of public criminal action when one of the parties is or conforms parts of the communities, peoples and indigenous nationalities. Key words: Constitutional law, effective judicial protection, indigenous justice, legal pluralism, crimes of public criminal action.